Clinical and epidemiological aspects of urogenital chlamidiosis of men - K. S. Akyshbayeva; K. M. Madibraimov; M. K. Mukazhanov (Андрология и генитальная хирургия, 2015)
Objectve: the study of the clinical and epidemiological features of urogenital chlamydia infection in men. Subjects and methods. We have studied 132 men with urogenital Chlamydia infection. Laboratory methods – polymerase chain reaction, ELISA, immunofluorescence, bacterioscopic, bacteriological. The sperms were examined in accordance with the WHO recommendations. Results. Сlinical and laboratory studies have revealed: the chronic infection in 84.9 %; prostatitis in 59.1 %, with its frequency higer with chronic course; pathospermia in 72.2 %; mixed infection in 67.4 % with greater frequency with mycoplasmas (49.4 %), Ureaplasma urealyticum (38.2 %) and Trichomonas vaginalis (47.2 %). Copulative function disorders in 40 % of men, significantly often observed violations of erection and ejaculation. Conclusions. Urogenital chlamydia infection – a cause of various disorders of the reproductive system, with its frequency higer in pathients with mixt-infection. Involvement of the reproductive glands (prostate, epididymis and others). In the inflammatory process manifested pathospermia and copulative dysfunctions.